2015
DOI: 10.3758/s13428-015-0592-1
|View full text |Cite
|
Sign up to set email alerts
|

Tutorial dialogues and gist explanations of genetic breast cancer risk

Abstract: The intelligent tutoring system (ITS) BRCA Gist is a Web-based tutor developed using the Shareable Knowledge Objects (SKO) platform that uses latent semantic analysis to engage women in natural-language dialogues to teach about breast cancer risk. BRCA Gist appears to be the first ITS designed to assist patients' health decision making. Two studies provide fine-grained analyses of the verbal interactions between BRCA Gist and women responding to five questions pertaining to breast cancer and genetic risk. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Previous research subjected BRCA Gist to three multi-site randomized, controlled experiments with women at two universities, and field experiments with a community sample of women recruited in upstate New York and women recruited on-line (Wolfe et al, 2015; Wolfe, Reyna et al, 2013; Widmer et al, 2015). Participants were randomly assigned to BRCA Gist , the NCI web pages about breast cancer and genetic risk, or a control group receiving an irrelevant tutorial.…”
Section: 32 the Efficacy Of Brga Gistmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research subjected BRCA Gist to three multi-site randomized, controlled experiments with women at two universities, and field experiments with a community sample of women recruited in upstate New York and women recruited on-line (Wolfe et al, 2015; Wolfe, Reyna et al, 2013; Widmer et al, 2015). Participants were randomly assigned to BRCA Gist , the NCI web pages about breast cancer and genetic risk, or a control group receiving an irrelevant tutorial.…”
Section: 32 the Efficacy Of Brga Gistmentioning
confidence: 99%
“…Our approach has been to develop an Intelligent Tutoring System (ITS) called BRCA Gist (BReast CAncer and Genetics Intelligent Semantic Tutoring) to help healthy women understand and make decisions about genetic testing for breast cancer risk (Wolfe et al, 2015). There is solid evidence of the effectiveness of BRCA Gist (Wolfe et al, 2015; Wolfe et al, 2013; Widmer et al, 2015). The purpose of the current investigations is to isolate the processing loci responsible for effective learning, comprehension, and decision-making when women interact with this ITS.…”
Section: 1 Introductionmentioning
confidence: 99%
“…BRCA Gist (Breast Cancer and Genetics Intelligent Semantic Tutoring) appears to be the first ITS applied to lay people’s medical decision making (Wolfe et al, 2015). BRCA Gist has been found to effectively help women understand and make decisions about genetic testing for breast cancer risk (Widmer et al, 2015; Wolfe, Widmer, Reyna, et al, 2013; Wolfe et al, 2015; Wolfe, Reyna, Brust-Renck, et al, 2013; Wolfe, Reyna, Widmer, et al, 2013). The goal of the research presented in this paper is to better understand the argument-based verbal interactions between BRCA Gist and research participants through a fine-grained analysis of tutorial dialogues and to examine the effectiveness of providing arguments on learning outcomes including content knowledge regarding genetic risk for breast cancer as presented by BRCA Gist , the ability to categorize women into levels of breast cancer risk, and gist comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…However, self-explanations in BRCA Gist are briefer, with users typically making about seven dialogue moves to form a gist explanation . Gist explanation requires a briefer explanation that emphasizes the bottom line meaning rather than verbatim knowledge, which requires an exact representation of stored knowledge (Widmer et al, 2015). The tutorial concluded with two tutorial dialogues in which participants were asked to first provide an argument for and then provide an argument against genetic testing for breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown that active engagement was causally related to increased knowledge (Chi, 2009; Wolfe, Britt, Petrovic, Albrecht, & Kopp, 2009; see also Widmer, Wolfe, Reyna, Cedillos-Whynott, Brust-Renck, & Weil, 2015). Although participants might come to a study with different levels of engagement, and that, in combination with the content of the tutorial, might be important in establishing commitments to healthy values and intentions.…”
Section: Discussionmentioning
confidence: 95%